2010
DOI: 10.1306/10130909046
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating hydrocarbon trap integrity during fault reactivation using geomechanical three-dimensional modeling: An example from the Timor Sea, Australia

Abstract: A B S T R A C TThree-dimensional (3-D) coupled deformation and fluid-flow numerical modeling are used to simulate the response of a relatively complex set of trap-bounding faults to extensional reactivation and to investigate hydrocarbon preservation risk for structural traps in the offshore Bonaparte Basin (Laminaria High, the Timor Sea, Australian North West Shelf ).The model results show that the distributions of shear strain and dilation as well as fluid flux are heterogeneous along fault planes inferring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 58 publications
(84 reference statements)
4
28
1
Order By: Relevance
“…Similar observations have been made on the Australian North West Shelf where a link between the formation of Late Cenozoic carbonate buildups and focussed hydrocarbon seepage along fault conduits and localised venting of gas at the seafloor is suggested (e.g. Hovland et al, 1994;O'Brien and Woods, 1995;Bishop and O'Brien, 1998;Lavering and Jones, 2001;O'Brien et al, 2002;Langhi et al, 2010). Relationship between mound complexes and seep in the central Ceduna Sub-basin.…”
Section: Fault-related Seepage Model For Mound Complexes In the Centrsupporting
confidence: 66%
“…Similar observations have been made on the Australian North West Shelf where a link between the formation of Late Cenozoic carbonate buildups and focussed hydrocarbon seepage along fault conduits and localised venting of gas at the seafloor is suggested (e.g. Hovland et al, 1994;O'Brien and Woods, 1995;Bishop and O'Brien, 1998;Lavering and Jones, 2001;O'Brien et al, 2002;Langhi et al, 2010). Relationship between mound complexes and seep in the central Ceduna Sub-basin.…”
Section: Fault-related Seepage Model For Mound Complexes In the Centrsupporting
confidence: 66%
“…The code has been previously applied to simulate rock deformation and fluid flow processes (e.g. Ord, 1991;Strayer et al, 2001;Gartrell et al, 2003Gartrell et al, , 2004McLellan et al, 2004;Schaubs et al, 2006;Zhang et al, 2009;Langhi et al, 2010).…”
Section: Modelling Methodologymentioning
confidence: 99%
“…The current work is the first modelling study focussing on the impact of fluid pressure on fault reactivation, and hence represents a helpful supplementary contribution to the extensive existing work and knowledge on fault development/reactivation and fluid flow in faults (e.g. Sibson, 1985Sibson, , 1995Ge and Gargen, 1994;Cox, 1995;Childs et al, 1996;Ge, 1997;Zhao et al, 2004Zhao et al, , 2006Garven et al, 2001;Stewart, 2001;Walsh et al, 2001;Dewhurst and Jones, 2003;Shipton and Cowie, 2003;Yang et al, 2004;Yang, 2006;Wibberley et al, 2008;Zhang et al, 2009;Langhi et al, 2010). It needs to be pointed out that "fault reactivation" concerned in this paper refers to the reactivation of pre-existing faults (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The complex linkages between shallow and deep fault systems have significant control on hydrocarbon preservation in the region (O'Brien et al, 1999;Cadman and Temple, 2004;Langhi et al, 2010Langhi et al, , 2011. In the Bonaparte Basin, 282 exploration wells have been drilled with 64 hydrocarbon discoveries (Geoscience Australia Offshore Petroleum Exploration Acreage Release 2014).…”
Section: Syn-collision Deformation Of Australian Marginmentioning
confidence: 99%
“…17) indicate a strong link between obliqueness of Neogene-Recent stress and trap integrity, despite uncertainty of actual leakage mechanism (Langhi et al, 2011 and references therein). It has been suggested that critical stressing of reservoir bounding faults (or fault segments) during Neogene-Recent is a major determinant of leak/seal potential Gartrell et al, 2006;Langhi et al, 2010Langhi et al, , 2011. Obliqueness of Neogene-Recent S Hmax relative to the Mesozoic faults varies mainly due to deviating Mesozoic trends across the margin and crookedness of individual fault planes (Fig.…”
Section: Vertical Linkages and Petroleum Implicationsmentioning
confidence: 99%